Integrating Family Support and Personal Counseling in a Behavioral Model for Tuberculosis Prevention - Sumiati, Sumiati; Suwarto, Suwarto; Wardani, Ratna; Wahyuningsih, Atik Setiawan (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2025)
ntroduction: Tuberculosis (TB) remains a major global public health problem in Indonesia, where household contact serves as the primary transmission pathway. Families, as the closest social units, play a crucial role in preventing TB spread; however, preventive behaviors often remain suboptimal due to fragmented and unsustained community interventions. Objective: This study aimed to develop and evaluate an integrative, family-based prevention model by positioning personal counseling as a mediator linking threat perception, coping appraisal, and family support with preventive behaviors. Methods: A two-phase quantitative study was conducted in Madiun City. Phase I involved 387 families of TB patients to analyze the relationships among variables using structural equation modeling–partial least squares (SEM-PLS). Phase II adopted a quasi-experimental design with intervention and control groups (n = 30 each) to assess the effectiveness of the integrative module. Statistical analyses included 95% confidence intervals (CIs) for all effect estimates. Ethical approval was granted by the Health Research Ethics Committee of Universitas Strada Indonesia (No. 2781/KEPK/IX/2023). Results: SEM-PLS analysis revealed that threat perception, coping appraisal, and family support significantly influenced TB preventive behaviors directly and indirectly through personal counseling (? = 0.01–0.35; 95% CI = 0.02–0.40; p < 0.05). The intervention significantly improved preventive behavior in the intervention group compared with the control group (mean increase = +7.5; 95% CI = +5.9–+9.1; p < 0.001). Conclusion: The integrative family-based model incorporating personal counseling effectively strengthened TB preventive behaviors among families. Theoretically, this study contributes to the integration of Social Cognitive Theory and Protection Motivation Theory in TB prevention, highlighting personal counseling as a behavioral mediator. Practically, this model can be adopted by primary healthcare providers and community health cadres to enhance family engagement and support Indonesia’s TB elimination targets by 2030. Study limitations include reliance on self-reported measures and a localized setting, which may constrain generalizability.